Measurable residual disease including AML leukemia stem cell flow evaluation of CPX-351 therapy by multi-parameter flow cytometry. (December 2021) - Plesa, Adriana; Roumier, Christophe; Gutrin, Joris; Larcher, Marie-Virginie; Balsat, Marie; Cadassou, Octavia; Barraco, Fiorenza; Fossard, Gaëlle; Baudouin, Amandine; Labussière, Hélène; Tigaud, Isabelle; Ducastelle, Sophie; et al.
Highlights: Our short series confirms the high response rate with CPX-351 in t-AML or MRC-AML. The high rate of MRD negativity supports prior evidence that CPX-351 contributes to long-term remission. MFC monitoring was confirmed as a reliable approach to assess response to treatment.